Targeting Autophagy to Treat Cancer: Challenges and Opportunities - Lim, Junghyun; Murthy, Aditya (Frontiers in Pharmacology, 2020)
Autophagy is a catabolic process that targets its cargo for lysosomal degradation. In addition to its function in maintaining tissue homeostasis, autophagy is recognized to play a context-dependent role in cancer. Autophagy may inhibit tumor initiation under specific contexts; however, a growing body of evidence supports a pro-tumorigenic role of this pathway in established disease. In this setting, autophagy drives treatment resistance, metabolic changes, and immunosuppression both in a tumor-intrinsic and extrinsic manner. This observation has prompted renewed interest in targeting autophagy for cancer therapy. Novel genetic models have proven especially insightful, revealing unique and overlapping roles of individual autophagy-related genes in tumor progression. Despite identification of pharmacologically actionable nodes in the pathway, fundamental challenges still exist for successful therapeutic inhibition of autophagy. Here we summarize the current understanding of autophagy as a driver of resistance against targeted and immuno-therapies and highlight knowledge gaps that, if addressed, may provide meaningful advances in the treatment of cancer.